Evaluating the effects of a tax increase : how the Swedish demand for snus will react to the new tax increase proposed by the government - Ericsson, Karin (SLU/Dept. of Economics, 2015)
This thesis deals with the concept of how price affects demand for a good by estimating various price elasticities of demand for snu sold in Sweden. Information was gathered on price development for snus and cigarettes as well as sales data from Swedish Match, the largest supplier of snus in Sweden. Income-, price- and cross-price elasticities were estimated based on log-log regression. Results show that snus is an inelastic good since the coefficient for price of snus was -0.536. This proved that a 1% increase in price causes a 0.536% decrease in quantity demanded. One of the main arguments from the government for increasing the tax on snus and thereby increasing price was to collect more tax revenue for reformations within the educational system. An elasticity of -0.536 indicates that an increase in tax will decrease demand and therefore also intended revenue. This proves that tax on snus should probably be lowered, since consumers have the possibility of choosing other products similar to snus such as cigarettes or moist snuff that is now considered equally expensive.